Medieval English Multilingualisms. Issue 1 (13th May 2020) - Critten, Rory G.; Dutton, Elisabeth
Abstract: This article introduces the nonmedievalist reader to the multilingual landscape of England 700–1400. Building on recent work exploring in particular the relationships among English, French, and Latin in medieval England, it discusses a series of "multilingual moments" from a range of sources, including letters, poems, travel writings, and French language teaching texts. Together, these examples build a picture of the complex interrelationships of languages, both spoken and written, that existed for medieval English people at home and when traveling abroad. Then, as now, people can be seen using their linguistic resources for pragmatic and creative effect. We demonstrate that multilingualism is nothing new. From a methodological perspective, our work also underlines the importance of viewing linguistic attitudes in their particular intellectual and historical contexts. Abstract :